1991
DOI: 10.1016/0014-5793(91)80518-8
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid sequences of jacalin and the Maclura pomifera agglutinin

Abstract: Amino acid sequences fo," tire ~.chains of Ih~ Moraceae leetins, ja~aiin and Mnchara ponlq~cru nsviutinin, w~re tielermined by protein sequen¢inv, Both arc 13)residues Ionli and eonlain several genetically variant positions; the overall homology is 8~'~. A possible :die for the known ltlYCOl~ptid,~ ol'jacalin was located, The =.chain= have a conserved tryptophaa residue that may he part of the binding,.site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…The sequence of the 250 amino acid polypeptide is identical to the recently published, conventionally derived, sequence of PNA [10], except for 14 additional amino acids at the C-terminal end. Recent analysis of the molecular size of mature PNA by mass spectrometry (N.M. Young, private communication) revealed that it consists of a major constituent of 236 amino acids (mol.…”
Section: Prepna-cdna Sequencingmentioning
confidence: 81%
See 2 more Smart Citations
“…The sequence of the 250 amino acid polypeptide is identical to the recently published, conventionally derived, sequence of PNA [10], except for 14 additional amino acids at the C-terminal end. Recent analysis of the molecular size of mature PNA by mass spectrometry (N.M. Young, private communication) revealed that it consists of a major constituent of 236 amino acids (mol.…”
Section: Prepna-cdna Sequencingmentioning
confidence: 81%
“…The hemagglutination studies prove that rPNA is functionally equivalent to native PNA. A single N-terminal sequence, Ala.Glu-Thr-Val-SerPhe-Asn-Phe-Asn-Ser-Phe-Ser, was found in rPNA, identical to that of the native lectin [10].…”
Section: 3mentioning
confidence: 81%
See 1 more Smart Citation
“…Heterogeneity (isolectins and N-glycosylation) is widely known in JRLs. [5][6][7]48) Sugar content of TAA-G was estimated to be less than 2.5 µg/mg protein (0.24 sugar residue/mole protein) by phenol-sulfuric method. Furthermore, no Asn-X-Ser (Thr) sequence was found in TAA-G.…”
Section: Discussionmentioning
confidence: 99%
“…4) gJRLs are synthesized as preproproteins, which undergo co-and post-translational processing, and built up of cleaved protomers, short β-chain and long α-chain. [5][6][7] On the contrary, mJRLs are not cleaved and have a single polypeptide chains. gJRLs are produced by the cleavage of a loop in mJRL homologs, resulting that gJRLs show the preference to galactose and N-acetyl galactosamine.…”
mentioning
confidence: 99%